2019
DOI: 10.1103/physrevmaterials.3.114408
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering measurement of crystalline-electric fields in magnesium rare-earth selenide spinels

Abstract: The symmetry of local moments plays a defining role in the nature of exotic grounds states stabilized in frustrated magnetic materials. We present inelastic neutron scattering (INS) measurements of the crystal electric field (CEF) excitations in the family of compounds MgRE2Se4 (RE ∈ {Ho, Tm, Er and Yb}). These compounds form in the spinel structure, with the rare earth ions comprising a highly frustrated pyrochlore sublattice. Within the symmetry constraints of this lattice, we fit both the energies and inten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…The accuracy of these studies was limited by their assumption of a perfect octahedral environment and also because magnetization data alone was used for the refinements of the CEF Hamiltonian. More recent studies have used inelastic neutron scattering to directly measure the CEF levels and find that although the ligands are a near perfect octahedra, the field from the next nearest neighbor creates a significant anisotropy along the local [111] directions, which is the axis that connects the centers of two adjacent tetrahedra [48][49][50]. The other major omission of the works prior to the new millennia is that they did not take into account the importance of geometric frustration, which explains their findings that none of these materials magnetically order above 2 K [43][44][45]51].…”
Section: Rare Earth Chalcogenide Spinelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The accuracy of these studies was limited by their assumption of a perfect octahedral environment and also because magnetization data alone was used for the refinements of the CEF Hamiltonian. More recent studies have used inelastic neutron scattering to directly measure the CEF levels and find that although the ligands are a near perfect octahedra, the field from the next nearest neighbor creates a significant anisotropy along the local [111] directions, which is the axis that connects the centers of two adjacent tetrahedra [48][49][50]. The other major omission of the works prior to the new millennia is that they did not take into account the importance of geometric frustration, which explains their findings that none of these materials magnetically order above 2 K [43][44][45]51].…”
Section: Rare Earth Chalcogenide Spinelsmentioning
confidence: 99%
“…There are conflicting reports on the spin anisotropy of the Yb 3+ moments, which can only partially be explained by material dependent parameters (the specific A and X ions). While one study found that the in-and out-of-plane components are nearly equal [62] and thus, Heisenberg-like, others have reported that it is weakly [63], or moderately Ising-like [50]. An exact identification of the ground state anisotropy is difficult because direct measurements of the CEF energy levels via neutron scattering leads to an underconstrained problem.…”
Section: B Ytterbium Chalcogenide Spinelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to facilitate the QSL search in the delafossites, it is crucial to have an overview of their CEF environment. As exemplified by the spin ice compounds [40][41][42][43], the CEF parameters in systems with similar structures normally obey the scaling rule. Therefore, compared to the Yb 3+ ions with J = 7/2 [35,39], rare earth ions with a larger J allow more CEF transitions, which will enable a more accurate fit of the CEF parameters and thus provide a reference in the study of the similar delafossite compounds.…”
Section: Introductionmentioning
confidence: 99%